Fitossociologia de plantas espontâneas e produção do milho verde inoculado em diferentes níveis de palha de babaçu - Cantanhede, Josilene Dias (2018)
Mulching is a cultural method used in the management of spontaneous plants that provides conditions for cultivated plants to express their productive potential and to obtain sustainable agricultural production. The objective of this work was to evaluate the population dynamics of the spontaneous vegetation and the crop production of the green corn inoculated with Azospirilum brasilense in different levels of babassu straw. The experiment was carried out in the 2016 harvest in an experimental area of the School Farm of the State University of Maranhão in São Luís - MA. The experimental design was a randomized block design in a 4 x 2 + 2 factorial arrangement with four replications. The treatments consisted of four quantities of crushed babassu straw (0, 15, 20, 25 t ha-1), two microbiological treatments (with and without inoculation of Azospirilum brasilense) and two additional controls with no babassu straw, presence of spontaneous plants and microbiological treatments. The phytosociological survey was performed at 20, 30, 40, 50 and 70 days after emergence of the crop for the straw treatments and at 70 days after emergence of the crop (harvest) only for the treatments with absence of babassu straw. The evaluations of the spontaneous plants were carried out by the method of the square inventory launched three times at random among the planting lines using a metallic square of 0.5 m x 0.5 m. The plants were cut, identified and oven dried at 65 ° C to obtain the dry matter. The phytosociological indices obtained were: relative density, relative frequency, relative dominance and importance value index. For the crop, stem diameter, plant height and spike insertion, length and diameter of commercial ears with and without straw and total yield of ears with straw and without straw were evaluated. The lowest amount of spontaneous species occurred in the presence of babassu straw and Azospirillum brasilense inoculation. The families Cyperaceae and Poaceae were relevant in green maize culture independent of mulching and microbiological treatments. The species Murdania nudiflora, Commelina benghalensis, Cyperus sphacelatus, Echinochloa colonum and Eleusine indica. They were suppressed by babassu straw and Azospirillum brasilense inoculation. The species with the highest importance value in the presence of babassu straw and microbiological treatments were Cissampelos glaberrima, Cyperus diffusus and Panicum trichoides. The yield of commercial ears without straw in the inoculation treatments was similar for all levels of babassu straw, ranging from 7,167.50 to 8,072 kg ha-1. For the treatments without inoculation was significantly higher in the treatment with 0 t ha-1 of straw, that is to say, with absence of straw and with weeding during the whole cycle of the crop (9.362,50 kg ha-1) in relation to the other straw levels. The presence of the dead mulch of babassu acts together with the inoculation Azospirilum brasilense in the green corn crop in the reduction of the richness of spontaneous plant species, suppressing some important species of the families Poaceae and Cyperaceae. The levels of babassu straw and the microbiological treatments do not act together on the heights of the corn plants, height of insertion of spike and diameter of the stem. However, they improve the productivity of commercial ears without green corn straw.